Peranan Pelayanan Antenatal K4 Dalam Mendeteksi Kejadian Anemia, Preeklamsi Berat, Eklamsi, Letak Sungsang dan BBLR Saat Persalinan di Wilayah Kerja Kecamatan Garut Kota Kabupaten Garut - Eneng Solihah (STIKes Karsa Husada Garut, 2015)
One of the efforts to decrese anemia, severe preeclampsia, eclampsia, breech presentation and LBW as the cause factors of high numbers of mother and babies mortality by antenatal care. The successful indicator is K4. The aim of research is to find out the role of antenatal service with K4 towards anemia, severe preeclampsia, eclampsia, breech presentation and LBW in labour in work area Garut Town Subdistrict. The method used in research is cohort prospective with observational approach to two groups of pregnant women in labour who make K4 visits both completely and incompletely in the occurrence of anemia, severe preeclampsia, eclampsia, breech presentation and LBW in labour. Analyzed uses chi square statistic test and coefficient contingency. Data sources come from primery; namely, pregnant women who meet inclusive criteria which are divided into two groups – a group with complete K4 service, and the other group with incomplete K4 service. Secondary data come from mothers cohort records in the research site. The result towards 60 respondents who become research objects show that characteristics of meaningless pregnant women towards antenatal service of K4 with grade > 0,05. The effect of K4 service towards anemia is found out grade p = 0,02 (p < 0,05), severe preeclampsia p= 0,301 (p < 0,05), eclampsia p = 0,313, breech pressententation p = 0,288 and LBW is 0,688. In conclusion from the research, find out that K4 antenatal visit has to act as to detect anemia occurrence in labour, but not for severe preeclamsi, eclampsia, breech presentation and LBW in labour.